Behaviour of a Segmental Tunnel Lining Under Seismic Actions. (2016) - Fabozzi, Stefania; Bilotta, Emilio
Abstract: Full dynamic analyses that follow a coupled approach for the soil-structure interaction, provides satisfactory interpretation of non-linear boundary problems during earthquakes. This paper illustrates the results of a numerical study aimed at modelling the performance of continuous and segmental linings of shallow tunnel under seismic loading. A set of 3D finite-element full dynamic analyses have been carried out, calibrated on the experimental results of a centrifuge test on a model tunnel in a dense dry sand layer subjected to transversal dynamic loading [1]. The numerical study was extended to model and compare the seismic demand of a continuous and a segmental reinforced concrete lining, including the effect of the excavation process on the pre-seismic conditions and the influence of different input signals. The results show that even in rather simple ground conditions, a suitable constitutive model for soil is needed to capture the effect of soil-lining interaction during and after the seismic event.